Penanganan Gagal Jantung Diastolik - Starry H. Rampengan (Jurnal Kardiologi Indonesia, 2014)
The diastolic heart failure also referred to as heart failure with preserved left ventricular systolic function (preserved ejection fraction). The difference between systolic and diastolic HFs is a pathophysiological one and isolated forms of left ventricular dysfunction are rarely observed. In diastolic HF left ventricular systolic function is normal or only slightly impaired, and the typical manifestations of HF result from increased filling pressure caused by impaired relaxation and compliance of the left ventricle. The management should include antihypertensive treatment, maintenanceof the sinus rhythm, prevention of tachycardia, venous pressure reduction, prevention of myocardial ischemia and prevention of diabetes mellitus. Treatment of diastolic HF is aimed to stop the progression of the disease, relieve its symptoms, eliminate exacerbations and reduce the mortality. The predisposing factors for diastolic dysfunction include elderly age, female sex, obesity, coronary artery disease, hypertension and diabetes mellitus. The European Society of Cardiology specifies the type of therapy in diastolic HF based on: angiotensin converting enzyme inhibitors, angiotensin receptor blockers, beta-blockers, non dihydropyridine calcium channel blockers, diuretics.